Music Education based on Competencies in Spain: Necessity or desire? - José Antonio Hernández-Bravo; Juan Rafael Hernández-Bravo; María del Valle de Moya-Martínez; Ramón Cózar-Gutiérrez (Revista Electrónica Educare)
This paper is aimed at critically analyzing the implementation of a system based on competencies in the Spanish curriculum, more specifically in music education. Our current society, subject to vertiginous transformations, is demanding an effective educational response, as well as updated teaching and learning processes. In this context, this study has confirmed the need for both teachers and learners to acquire practical skills and to use active methodologies in the music field. Consequently, curricular contents will become of secondary importance and emphasis will be given to developing competencies that enable individuals to perform tasks and solve problems in real life situations. However, taking into account the importance still given to the traditional expository lecture approach, these changes raise questions about its viability in schools. Due to the inherent nature of music, working with competencies is more adequate in music than in other subjects, and, although its use is necessary to introduce students to music, reality is different than what is desired. The novelty of the topic and its practical implications make it a focus of interest for studies and reflections, like the one presented in this paper, in order to get a better understanding of this phenomenon and establish effective educational actions.